A Discussion for Alternative Affordable Housing Types: Comparative Analysis of Urban Informalities - Küçükyazıcı, Ufuk; Alkışer Bregger, Yasemin (My University, 2019)
Finding a shelter to dwell in at a reasonable price is a problematic issue for urban areas all over the world due to high values of urban land, lack of regulations about housing, and inequalities of income in society. The demand for affordable housing is increasing parallel to the rise in urban population caused by migration. Especially after industrialization, the accommodation requirements of low-income and middle- income groups in the global north were acknowledged by authorities, planners and architects in order to support development in terms of social structure, built environment and the economy. Consequently, there are studies of alternatives for housing policies in order to provide either owner-occupied houses or rental homes for the urban poor. Housing studies of western culture have impact on developing new strategies all over the world. On the other hand, in the global south, the development of economic system continues to result in migration to urban areas. Even though the major amount of the expansion in urban areas happens in developing countries, the need for affordable housing is a universal issue. The increase in population creates problems on finding equal housing options among different income levels of society for accommodating sufficient housing in the urban structure. When the demand for low-income housing units is not efficiently responded to, citizens develop their own way to create accommodation options in reasonable prices in the form of informal settlements which might have different urban characteristics according to the development level of the country, climate, and culture. However, the main purpose of squatters all over the world is to find shelter to live in so as to survive in the urban life. The changes in city formations and infrastructure requirements of urban land caused by informal solutions for housing have impact on urban development. This in turn affects the policies of urban transformation. Under these circumstances, reciprocal relations might become prominent between urban transformation and affordable housing studies. A clear definition of affordable housing is essential in order to determine concrete solutions, because the wide meaning of affordability as the status for being able to buy something creates general assumptions. The housing type that costs less than thirty percent of the total income of the households would be considered as affordable housing. In fact, this concept applies to all segment of society however; the problem mostly occurs in terms of low-income housing due to insufficient income levels, increasing land values, and property costs. In this study, the informal solution for affordable housing and the consequences in terms of urban transformation process is examined in two sections. In the first part, the definition of affordable housing is evaluated by giving policy explanations and informal solutions which have occurred as self help interventions of citizens. In addition, the comparative housing analyses approach is defined in order to explain current discussions about affordable housing studies. In the second part, affordable housing concepts in the Netherlands and Turkey are discussed through comparative analysis in order to explain the differences and similarities of housing problems in developed and developing countries. Alternative ways of affordable informal housing opportunities are evaluated in terms of the consequences of urban development through examples from Netherlands (squatter movements), and Turkey (squatter settlements) in order to explain the relation among affordable housing, urban informalities and urban transformation. The examples show the changes of urban structures due to affordable housing demand and the self-help of citizens. The reason for choosing examples from Netherlands is their detailed affordable housing system. Despite housing regulations there are also informal solutions. Informal solutions are shown to discuss the need for affordable housing, the lack of response for the demand and also the possibilities of emergent solutions of the citizens for their own problems. These emergent informal solutions have impact on the formations of cities.
Keywords: Affordable Housing; Squatter Movements; Squatter Settlements; Urban Transformation; Alternative Accommodation Types; Uygun Fiyatlı Konut; Gecekondu Hareketi; Gecekondu Yerleşimleri; Kentsel Dönüşüm; Alternatif Konaklama Türleri